HUBUNGAN TINGKAT PENGETAHUAN TENTANG KEBUTUHAN CAIRAN TUBUH DENGAN POLA KONSUMSI AIR MINUM PADA MAHASISWA TINGKAT I AKPER PANTI KOSALA SURAKARTA - Budi Herminto; Risa Setia Ismandani (KOSALA : Jurnal Ilmu Kesehatan, 2016)
AbstractWater represent compound which is the necessary for all living. Consumption behaviorirrigate society not yet altogether goodness, society consume water when feel thirsty anddo not so pay attention drinking water and amount matching with requirement. Purpose ofthe study to determine the relationship between the knowledge level about fluid bodyrequirement with pattern consume drinking water at student in Academy of Nursing PantiKosala Surakarta.The subject was used as population in the study was all the first year students. The totalpopulation were 139 students, and the sample were 103 students. The samplingtechnique was simple random sampling.This research method represent analytic research with design research of corelasional toknow relationship between knowledge level about fluid body requirement with patternconsume drinking water of student.The results was the high level of knowledge about the fluid body requirment were 74(72%), moderate level of knowledge about the fluid body requirment were 29 (28%), whilethe behavior of consuming appropiate water were 69 (67%), and the behavior ofconsuming inappropiate water were 34 (33%) with a p-value 0.003 <0.05 significant 95%.There was a significant relationship between the knowledge level about fluid bodyrequirement with pattern consume drinking water at student in Academy of Nursing PantiKosala Surakarta.Keywords: knowlegde level, fluid body requirement, pattern consume drinking water.